Honey-borne infant botulism in tahnik practice: an explanation of the risk and its solutions - Harun, Mohammad Amir Wan; Abdullah, A.; Mohamad, A.M.; Baharuddin, A.S. (Rynnye Lyan Resources, Malaysia, 2021)
Tahnik is a primarily Islamic practice wherein a newborn’s palate is daubed with dates or honey. However, feeding honey to an infant has been associated with numerous infant botulism cases. This situation has raised the question of how a religious practice could lead to such a severe health risk? The objectives of the study were to investigate: a reliable method of performing tahnik; the original proposition of using honey in tahnik; and the efficacy of using ingredients other than dates in tahnik. Semi-structured interviews and armchair research methods were utilised to gain data from three Islamic scholars. Other resources were also consulted, including the United States Department of Agriculture (USDA) Food Composition Database and various Islamic Literary Manuscripts. The findings indicated that the use of honey in tahnik did not originate within Islamic jurisprudence. Therefore, it should not be associated with the Prophet's Sunnah. When dates are not available for tahnik practice, then raisins, figs, pomegranates, grapes, or other sweet fruits can be used as a replacement rather than honey.